Processo de implementação da vigilância do câncer relacionado ao trabalho em Minas Gerais e seu impacto nas notificações de mesotelioma no sistema de informação de agravos de notificação - Cristiane Moreira Magalhães Andrade (2023)
In Minas Gerais, mesothelioma, a rare occupational tumor par excellence, is underreported in the Notifiable Diseases Information System - SINAN, due to various factors such as the lack of continuous, systematic and routine Work-Related Cancer Surveillance (VCRT) actions. The aims of this study were to describe the process of implementing VCRT in Minas Gerais and to assess its impact on mesothelioma notifications on SINAN. Methods: A case study was used to describe the process of implementing the VCRT, and a descriptive cross-sectional study, based on the analysis of secondary data from the SINAN Work-Related Cancer forms, with the specific diagnosis field filled in with ICD C45 - mesothelioma, to verify the sensitivity and qualification of the notifications. Descriptive analyses were carried out using frequency distribution tables, using Statistical Package for Social Science (SPSS) software version 19.0. Results: It was found that the structuring of the VCRT in the state was based on the establishment of intra- and intersectoral partnerships. Actions were initially centered on the epidemiological surveillance of neoplasms, with mesothelioma chosen as the priority cancer and the Belo Horizonte Regional Health Unit (URS) as the pilot for implementing the VCRT. The active search for cases took place via the Health Information Systems (SIS), especially the Hospital Cancer Registry and the Mortality Information System (SIM). The SIS identified 114 cases of mesothelioma, which were investigated by the municipal Occupational Health Surveillance services (VISAT) in order to verify the relationship between the disease and work. The occupational history survey, an essential step, was carried out mainly by applying a specific form and interviewing (most of) the family members or workers. In some cases, unions and universities were involved to characterize the risk. Medical records were also analyzed. However, most of them did not record information of importance to Workers' Health, such as occupation. SIM information was qualified, including diagnosis, based on the mesothelioma investigations carried out. Due to the complexity of the actions, there was a need to improve the awareness of the High Complexity to identify cases in a timely manner, as well as to qualify the information of interest to workers' health in the care records. As VCRT progressed in the state, actions were expanded to other URS and to other types of cancer (leukemia, non-Hodgkin's lymphoma in farmers and non-melanoma skin cancers in high-risk occupations), as well as promoting the Surveillance of Work Environments and Processes in establishments exposed to carcinogens. As for mesothelioma notifications, there was a significant increase in the number of cases registered, from 4 before to 35 after the implementation of the VCRT. Of these, the majority were male, worked as bricklayers, had a lower level of education and lived in the municipalities covered by the URS BH. As a technical product, a document was drawn up with guidelines to support the implementation of VCRT actions by health professionals, especially those from VISAT, with a focus on epidemiological investigations into occupational health in cases of suspected work-related cancers. This experience, specific to mesothelioma, showed that the actions can be applied to any type of cancer and carried out by all VISAT services, taking into account local and regional specificities. It was also found that the analysis of SINAN data was very important for identifying and better characterizing the epidemiological profile of workers affected by mesothelioma in the state.